2022
DOI: 10.1177/20503121221112485
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related problems and associated factors among adult psychiatric inpatients in Northwest Ethiopia: Multicenter cross-sectional study

Abstract: Objective: To determine the prevalence of drug-related problems and the factors influencing them among adult psychiatric inpatients. Methods: A multi-centre cross-sectional observational study was conducted from April to July 2021 at five randomly selected hospitals in Northwest Ethiopia. A total of 325 consecutively sampled patients participated in the study. Clinical pharmacists assessed the drug-related problems based on clinical judgement supported by updated evidence-based disease guidelines. We used the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Even though there is a single study that demonstrated drug-drug interactions in patients with psychiatric disorders, it was a single-center study with a retrospective cross-sectional design [8]. The current multicenter study was part of a project initially published regarding the prevalence of drug-related problems (DRPs) [9]. The initial study couldn't address a detailed investigation of the extent of drug-drug interactions and its determinants.…”
Section: Introductionmentioning
confidence: 99%
“…Even though there is a single study that demonstrated drug-drug interactions in patients with psychiatric disorders, it was a single-center study with a retrospective cross-sectional design [8]. The current multicenter study was part of a project initially published regarding the prevalence of drug-related problems (DRPs) [9]. The initial study couldn't address a detailed investigation of the extent of drug-drug interactions and its determinants.…”
Section: Introductionmentioning
confidence: 99%
“…Even though there is a single study that demonstrated drug-drug interactions in patients with psychiatric disorders, it was a single-center study with a retrospective cross-sectional design [8]. The current multicenter study was part of a project initially published regarding the prevalence of drug-related problems (DRPs) [9]. The initial study couldn't address a detailed investigation of the extent of drug-drug interactions and its determinants.…”
Section: Introductionmentioning
confidence: 99%